(untitled) (Colombia Medica, 1981)
To examine the permeability of developing follicles in vampire bat Desmodus rotundus ovaries, an intercellular tracer with enzymatic characteristics, horseradish peroxidase was used. At different intervals after intravenous tracer injection, the ovaries were removed. Results indicate that peroxidase readily passes across the blood capillaries endothelial wall, its basement lamina, from which it moves through connective tissue cells forming the theca. The tracer permeates the perifollicular basement lamina and accumulates among follicle cells for suturing the zona pellucida of secondary, tertiary, and preovulatory follicles; however, it is not incorporated by the latter oocyte. This is in contrast with the follicles oocytes in other maturational stages. Therefore, it is suggested that in the preovulatory stage, the barrier to the peroxidase-free uptake is primarily located in the oolema of oocytes.